A contribuição do geomarketing nas organizações - Fagundes, André Francisco Alcântara (2006)
This dissertation has verified the contribution that geomarketing - a tool which uses computational techniques and geographical data in order to generate information in digitalized maps - has given to the decision-making process of marketing in the main corporate groups of Uberlândia-MG. The research had as its focus the verification of the contribution of geomarketing in the following marketing activities: market segmentation, sales management, market potential analysis and business localization. The method used was cases study and the companies researched belong to the ten corporate groups in town which achieved the best finantial results in 2004. The data were collected by means of interviews with the people in charge of the marketing or geomarketing area of the researched companies. Content and documental analysis have been used for the analysis of the data collected. It has been concluded that geomarketing contributes to the marketing area in the decision making process, especially when it comes to quality and accuracy of the reports that it releases to its users, which, due to the innovative way of mixing marketing data with maps, allows a faster and more efficient comprehension of the analysed market circumstances. Besides, even if geomarketing doesn t present innovations related to the marketing theory, it consists of a tool which brings more positivity to the marketing area. The research has also shown that the use of geomarketing is more useful for the companies which have a larger number of clients, actual and potential, especially in situations in which these clients are geographically dispersed in their market.